PENERAPAN METODE K-MEANS UNTUK CLUSTERING PENGUNJUNG PERPUSTAKAAN ITN MALANG - Febrianto, Andy; Achmadi, Sentot; Panji Sasmito, Agung (Institut Teknologi Nasional Malang, 2021)
Library of National Istitute Of Technology Malang is one of the facilities and infrastructure that provides various services for providing academic information, while there are collections such as research results, papers, articles, theses and postgraduate theses, there is loan transaction data so far not used further. to also explore patterns of information that might be valuable for use in evaluating book collections and other documentation. Researchers have initiated to produce an application that can group visitors and borrowers using the K-Means method, helping librarians to evaluate information on visits and book borrowing in the ITN Malang library. This research is a Research and Development research based on website-based applications, the method used is the K-Means method, for thesis product develope that needed include system only used for computers , the system can only be accessed by ITN Malang library staff. The results of this study are a product in the form of a website application, the product has a feature, namely the system on the website can provide analysis of information on visitors and borrowers, based on functional testing the whole system is successful and running well, based on user testing, it is known that the percentage of respondents is 50% Very Good, 48% Good and 2% Not Good, based on research concluded that all features can run well on the Mozilla Firefox 83.0 and Google Chrome 87.0.4280.88 browsers, based on testing the majority of users rated very well on application usage.